2010
DOI: 10.1021/je9009915
|View full text |Cite
|
Sign up to set email alerts
|

pTx Measurements for Some Working Fluids for an Absorption Heat Transformer: 1,1,1,2-Tetrafluoroethane (R134a) + Dimethylether Diethylene Glycol (DMEDEG) and Dimethylether Triethylene Glycol (DMETrEG)

Abstract: The solubilities of 1,1,1,2-tetrafluoroethane (R134a), CF3CH2F, + dimethylether diethylene glycol (DMEDEG), CH3O(CH2CH2O)2CH3, and R134a + dimethylether triethylene glycol (DMETrEG) binary systems were measured, using the “static−analytic” method at temperatures between (303 and 353) K. This work was an opportunity to test the use of R134a as a refrigerant in combination with an organic absorbent, like DMEDEG and DMETrEG, in an absorption heat transformer (AHT), also known as a type II absorption heat pump or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 23 publications
1
24
0
Order By: Relevance
“…Previous works carried out by the same present authors are reported in the literature and one can cite Zehioua et al 2,3 . who considered the modeling and experimental measurements of isothermal vapor-liquid equilibrium data for different binary systems namely 1, 1, 1, 2-Tetrafluoroethane (R134a) + Dimethylformamide (DMF) working fluids used for an Absorption Heat Transformer (AHT) 2 and R134a + 1-Methoxy-2-(2methoxyethoxy) ethane (DMEDEG) and 1,2-bis(2-ethoxyethoxy) ethane (DMETrEG) 3 . Also…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…Previous works carried out by the same present authors are reported in the literature and one can cite Zehioua et al 2,3 . who considered the modeling and experimental measurements of isothermal vapor-liquid equilibrium data for different binary systems namely 1, 1, 1, 2-Tetrafluoroethane (R134a) + Dimethylformamide (DMF) working fluids used for an Absorption Heat Transformer (AHT) 2 and R134a + 1-Methoxy-2-(2methoxyethoxy) ethane (DMEDEG) and 1,2-bis(2-ethoxyethoxy) ethane (DMETrEG) 3 . Also…”
Section: Introductionsupporting
confidence: 59%
“…Previous works carried out by the same present authors are reported in the literature, and one can cite Zehioua et al , who considered the modeling and experimental measurements of isothermal vapor–liquid equilibrium data for different binary systems, namely, 1,1,1,2-tetrafluoroethane (R134a) + dimethylformamide (DMF) working fluids used for an absorption heat transformer (AHT) and R134a + 1-methoxy-2-(2-methoxyethoxy) ethane (DMEDEG) and 1,2-bis­(2-ethoxyethoxy) ethane (DMETrEG) . Also Fatouh and Murthy considered different working fluid pairs on the basis of p – T – x – H data, with R22 as the refrigerant and six different organic absorbents: [ N , N -dimethylformamide (DMF), N , N -dimethylacetamide (DMA), N -methyl-2-pyrrolidone (NMP), dimethyl ether diethylene glycol (DMEDEG), dimethyl ether tetraethylene glycol (DMETEG), and dimethyl ether triethylene glycol (DMETrEG)] still used in AHT.…”
Section: Introductionmentioning
confidence: 99%
“…In order to measure the VLE data of R124-NMP and R124-DMF binary mixtures, the experimental principle given by refs , , and was adopted in this paper and a VLE measurement system showed in Figure was set. The system composed of some apparatuses which are (1) thermostatic water bath, (2) equilibrium still, (3) temperature controller, (4) refrigerator, (5) vacuum pump, (6) temperature sensors, (7) pressure sensors, (8) refrigerant cylinder, (9) refrigerant storage tank, (10) valves, (11) computer, (12) liquid injector, (13) six-way metering valve, and (14) gas chromatography (GC).…”
Section: Vle Measurement Sectionmentioning
confidence: 99%
“…In order to replace two traditional working fluids, many efforts have been paid to research and develop new organic working fluids in which the refrigerants are hydrochlorofluorocarbons (HCFCs) or hydrofluorocarbons (HFCs), such as R22, R124, and R134a, and the absorbents are chemical solvents, such as N , N -dimethylformamide (DMF), N , N -dimethylacetamide (DMAC), N -methyl-2-pyrrolidone (NMP), dimethyl ether diethylene glycol (DMEDEG), dimethyl ether tetraethylene glycol (DMETEG), and dimethyl ether triethylene glycol (DMETrEG). Although the ozone depletion potential (ODP) of these refrigerants may not be zero and the global warming potential (GWP) of these refrigerants may be high, the influence on the environment is comparatively small when refrigerants leak from ARSs due to most refrigerants stay in ARSs in the form of solution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation